Management of Adult Patients with Perioperative Pulmonary Hypertension: Technical Aspects and Therapeutic Options - Winterhalter, Michael; Antoniou, Theofani; Loukanov, Tsvetomir (Cardiology, 2010)
Pulmonary hypertension (PH) is an independent risk factor for increased mortality in patients undergoing heart surgery. Existing chronic PH may be exacerbated by acute post-bypass PH, and this can lead to acute right ventricular failure. The prevention and treatment of right ventricular failure in cardiac surgery is based on three principles: optimize right ventricular preload, improve right ventricular contractility, minimize right ventricular afterload. The last of these may involve specific measures such as the inhalation of nitric oxide (NO) or of the stable prostacyclin analogue iloprost. The advantage of these inhalable substances is their pulmonary selectivity, and the subsequent reduction in systemic side effects. In order to avoid disastrous results in high-risk cardiac surgical patients, intra- and post-operative monitoring with pressure lines, a qualified team that pays attention to details, and an aggressive and early treatment in the operating room with inhaled iloprost and/or NO is necessary. The philosophy of ‘wait and see’ should be abandoned in favour of ‘be suspicious and act early’. In a prospective randomized trial, the efficacies of inhaled iloprost and of inhaled NO in the therapy of PH immediately following weaning from cardiopulmonary bypass in cardiac surgical patients were compared. Iloprost proved to be significantly more effective with respect to mean pulmonary arterial pressure, pulmonary vascular resistance, and cardiac output than inhaled NO.
Gesehen am 26.02.2024